Use of horse riding in chronic pain therapy - Sylwia Mazur; Agata Mazur; Magdalena Madera; Aleksy Bizan; Emilia Nagórska; Krzysztof Marcinkowski; Karolina Strus; Aleksandra Kublińska; Roksana Zdunek; Natalia Dąbrowska (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Chronic pain is a struggle itself and also a symptom in many common conditions. Its complexity requires diverse treatment methods including some that might seem unconventional, for example, horse riding. This study gathers information about the use of equine assisted therapy in pain relief.